Ação protetora do licopeno sobre as alterações induzidas pela micotoxina zearalenona em camundongos machos - Boeira, Silvana Peterini (2015)
Zearalenone (ZEA) an estrogenic mycotoxin and, therefore the reproductive system as one of its main targets of toxicity. Besides being a mycotoxin and toxigenic immunosuppressive, the ZEA hematological changes and promotes an imbalance in the oxidative system, especially in antioxidant enzymes. Thus, lycopene, a carotenoid antioxidant potential is considered one of the most potent free radical scavengers and may be used as an alternative therapy to reduce or prevent the toxic effects of ZEA. Male Swiss mice were pretreated with lycopene (20 mg/kg, p.o.) for 10 consecutive days. On the 11th day was held the acute treatment with ZEA (40 mg/kg, p.o.), and after 48 hours was performed euthanasia of animals. We analyzed reproductive, hematological, histological, inflammatory and oxidative stress markers in blood, testes, epididymis, kidneys and livers. ZEA hematotoxicity caused by increased total leukocytes and hemoglobin and hematocrit increased and decreased the number of lymphocytes as well as erythrocytes and platelets. In regard to reproductive and hormonal parameters changes in testicular histology and decreased testosterone levels and sperm motility and count were observed. The activity of GST (Glutathione-S-transferase), GR (Glutathione reductase) and ALA-D (delta aminolevulinic acid dehydratase) was reduced by the action of ZEA in the testes. The glutathione system was amended by ZEA by decreasing the reduced glutathione (GSH) and increased oxidized glutathione (GSSG) and GSH / GSSG. The analyzed pro-inflammatory parameters were increased by the action of mycotoxin. Pretreatment with lycopene prevented the onset of toxic effects induced by ZEA in virtually all parameters and thus, this antioxidant may be used as an alternative to the prevention of damage by ZEA.